KARAKTERISASI ABU KAYU MERBAU (Intsia, spp.): PENGARUH TEMPERATUR DAN LAMA KALSINASI - Darma Santi; Jacson Victor Morin (Jurnal Natural, 2019)
Characterization of merbau wood ash (Intsia, spp.) due to the influence of temperature and time of calcination has been studied. The variations in calcination temperature were 500 ᴼC (as M500) and 600 ᴼC (as M600), while the variations in the duration of calcination were 1, 2, and 3 hours, noted as M1, M2, and M3, respectively. Characterization was carried out using X-ray diffraction (XRD) and spectroscopic analysis using FT-IR. XRD results identified the presence of CaCO3 species (rhombohedral structure) and K2Si4O9 species with a hexagonal structure on M500. The M600 species identified Si (cubic structure), SiO2 (cubic structure), K2Si4O9 (hexagonal structure), and CaCO3 (rhombohedral structure). In general, the calcination temperature increases the crystallinity of several compounds contained in merbau wood ash. The length of time calcination reduces the absorption peak due to the decomposition and adsorption reactions of the presence of water molecules bound to the ash material of merbau wood (Intsia, spp).